Analysis of Teacher Performance Assessed from the Aspects of Organizational Culture, Motivation, and Competence - Silalahi, Marto; Simatupang, Sudung; Romy, Elly; Candra, Vivi; Sudirman, Acai (LPPM Undiksha, 2021)
To support the optimal implementation of education, every educational institution, including schools, strives to improve the performance of their teachers. The stimulus that can be given to make this happen can be in the form of implementing organizational culture, providing motivation, and increasing competence. The substance of this study is to determine the effect of organizational culture, motivation, and competence on teacher performance. The sample in this study amounted to 215 respondents who were determined by the purposive sampling approach. Data analysis using the SPSS application by displaying the results of data processing through test research instruments with validity and reliability, multiple regression analysis, the coefficient of determination, and hypothesis testing. The results of this study indicate that of the three developed hypotheses, all hypotheses are accepted. The first hypothesis shows that there is a significant influence of organizational culture on teacher performance. This is important for schools to pay attention to regarding the application of organizational culture. The implementation of an organizational culture that is too rigid will lead to a less than optimal work culture. Furthermore, the second hypothesis shows that motivation has a significant effect on teacher performance. To be able to increase the motivation of teachers, the school can give appreciation for their work so that teachers are more enthusiastic and can improve the quality of their work, it is better if teachers increase their enthusiasm so that whatever work is assigned can be completed with satisfactory results. Then, the third hypothesis shows that there is a significant effect of competence on teacher performance. There needs to be encouragement from the school for teachers to improve their competence. It is better if school principals need to motivate teachers, especially senior teachers, to participate in training and develop their competencies.